Given the equation
"(x^2D^2-3xD + 1)y= x^{-1} [1 + logx sin (logx)]"
which is a homogeneous linear equation. Let "x=e^z", that is "z=log\\ x", then the equation becomes;
"(D_1(D_1-1)-3D_1+1)y=e^z(1+z\\sin z)\\\\\n\\implies (D_1^2-4D_1+1)y=e^z(1+z\\sin z)"
Hence the auxiliary equation is
"(D_1^2-4D_1+1)y=0\\\\\n\\implies D_1=\\frac{4 \\pm \\sqrt{12}}{2}=2 \\pm \\sqrt{3}"
Hence "C.F=C_1e^{(2+\\sqrt{3})z}+C_2e^{(2-\\sqrt{3})z}"
"C.F=C_1e^{(2+\\sqrt{3})log x}+C_2e^{(2-\\sqrt{3})log x}\\\\\n\\implies C_1x^{2+\\sqrt{3}}+C_2x^{2-\\sqrt{3}}\\\\\n\\implies x^2(C_1x^{\\sqrt{3}}+C_2x^{-\\sqrt{3}})"
Now,
For "e^{-z}(z\\ sin z)"
"P.I_1=\\frac{1}{D^2_1-4D_1+1}e^{-z}(z\\ sin z)\\\\\n\\implies e^{-z}\\frac{1}{(D_1-1)^2-4(D_1-1)+1}(z\\ sin z)\\\\\n\\implies e^{-z}\\frac{1}{(D_1^2-6D_1+6)}(z\\ sin z)\\\\\n\\implies e^{-z}[z \\frac{1}{D_1^2-6D_1+6}sin z-\\frac{1}{(D_1^2-6D_1+6)^2}(2D_1-6)sin z]\\\\\n\\implies e^{-z}[z \\frac{1}{D_1^2-6D_1+6}sin z-\\frac{1}{(D_1^2-6D_1+6)^2}(2cos z-6sin z)]\\\\\n\\implies e^{-z}[z \\frac{1}{5-6D_1}sin z-\\frac{1}{(5-6D_1)^2}(6sin z-2cos z)]\\\\\n\\implies e^{-z}[z(5+6D_1) \\frac{1}{25-36D_1^2}sin z-\\frac{1}{25-60D_1+36D_1^2}(6sin z-2cos z)]\\\\\n\\implies e^{-z}[z(5+6D_1) \\frac{1}{61}sin z-\\frac{1}{-11-6-D_1}(6sin z-2cos z)]\\\\\n\\implies e^{-z}[\\frac{z}{61}(5sin z +6cos z)-(60D_1-11)\\frac{1}{3600D_1^2-121}(6sin z-2cos z)]\\\\\n\\implies e^{-z}[\\frac{z}{61}(5sin z +6cos z)+(60D_1-11)\\frac{1}{3721}(6sin z-2cos z)]\\\\\n\\implies e^{-z}[\\frac{z}{61}(5sin z +6cos z)+\\frac{1}{3721}(-360cos z-120sin z-66sinz-22cos z)]\\\\\n\\implies e^{-z}[\\frac{z}{61}(5sin z +6cos z)+\\frac{1}{3721}(-382cos z-54sin z)]\\\\\n\\implies x^{-1}[\\frac{log x}{61}(5sin (log x) +6cos (log x))+\\frac{1}{3721}(-382cos (log x)-54sin (log x))]\\\\"
"\\therefore P.I_1= x^{-1}[\\frac{log x}{61}(5sin (log x) +6cos (log x))+\\frac{1}{3721}(-382cos (log x)-54sin (log x))]"
Now, for "e^{-z}" where "D_1=-1"
"P.I_2=\\frac{1}{D_1^2-4D_1+1}e^{-z}\\\\\nP.I_2=\\frac{1}{(1)^2-4(1)+1}e^{-z} \\implies \\frac{1}{(1-4+1)e^{-z}}=\\frac{1}{6}x\\\\"
Hence the general solution is "y=C.F+P.I_2+P.I_1"
"y=x^2(C_1x^{\\sqrt{3}}+C_2x^{-\\sqrt{3}})+\\frac{1}{6}x+x^{-1}[\\frac{log x}{61}(5sin (log x) +6cos (log x))+\\frac{1}{3721}(-382cos (log x)-54sin (log x))]"
Comments
Leave a comment